Pulmonary rehabilitation program is an effective treatment approach for post-Covid-19 syndrome patients - Pádua, Karina (2024)
Background/Objectives: Patients with post-COVID-2019 syndrome may have reduced functional capacity and physical activity levels. The pulmonary rehabilitation program (PRP)—an exercise training program—is designed to restore these functions and has been shown to improve dyspnea, exercise capacity, and other measures in these patients. This study aimed to analyze the effects of the RP on post-COVID-19 syndrome patients with respect to objective and subjective functional capacity, balance, and musculoskeletal strength. Methods: A prospective interventional trial was conducted before and after this phase. Patients were referred to the hospital with a confirmed diagnosis of SARS-CoV-2 and subsequently directed to the RP. These patients underwent an 8-week pulmonary rehabilitation program (45-min sessions 3 times/week). Each session consisted of stationary cycleergometer and resistance musculoskeletal exercises tailored to individuals’ performance. They were evaluated pre- and post-PRP using the maximal handgrip strength (HGS) test, timed up-and-go test, 6-min walk test and its derived variables, and Duke Activity Status Index questionnaire. Results: From 142 hospitalized patients admitted with a diagnosis of SARS-CoV-2 infection, 60 completed the program, with an attendance rate of 85%. Nineteen patients were categorized as severe/critical, with a significantly higher hospital stay, compared to mild/moderate patients, and there were no differences in terms of sex distribution, age, or BMI between groups. Compared to the pre-PRP evaluation, both groups showed significant (p < 0.001) improvements in TUG, HGS, DASI D6MWT, 6MWS, and DSP variables after the PRP conduction. In addition, the groups exhibited similar improvement patterns following PRP (intragroup analysis), with no intergroup differences. Conclusions: RPs promote both objective and subjective functional capacity in patients with post-COVID-19 syndrome, with no difference in improvement regardless of the severity of the initial infection.